2022
DOI: 10.1002/smtd.202101089
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Kinematics of Sperm Motion by Reconstructing the Flagellar Wave Motion in 3D

Abstract: The flagellar wave originates from the 9+2 axoneme structure at the central core of the flagellum, where nine pairs of outer microtubule doublets are mechanically linked to a central pair. [2] The sequential sliding of the nine outer microtubules via dynein arms over the neighboring doublet bends the flagellum in 3D to produce a flagellar waveform. [3] This beating behavior is self-regulatory in nature, triggered by the combined activity of dynein motors. [3a,4] Several regulation mechanisms have been sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 79 publications
(75 reference statements)
0
11
0
Order By: Relevance
“…Incorporating more detailed morphological and mechanical features may be essential to capture certain characteristics of sperm locomotion [44] and may also help shed light on variations in sperm performance [45]. Our current model is also limited to planar deformations, while recent experimental evidence suggests that flagellar deformations may in fact be three-dimensional [46,47]: accounting for 3D deformations would require a more detailed description of the axonemal structure and of the elastodynamics of the flagellum, for instance as an active Kirkhoff rod [27]. Other improvements to the present work could include a model for internal dissipation inside the flagellum, which may be significant as suggested by recent observations [48], as well as for the coupling of dynein activity with calcium signaling [23,25,49].…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating more detailed morphological and mechanical features may be essential to capture certain characteristics of sperm locomotion [44] and may also help shed light on variations in sperm performance [45]. Our current model is also limited to planar deformations, while recent experimental evidence suggests that flagellar deformations may in fact be three-dimensional [46,47]: accounting for 3D deformations would require a more detailed description of the axonemal structure and of the elastodynamics of the flagellum, for instance as an active Kirkhoff rod [27]. Other improvements to the present work could include a model for internal dissipation inside the flagellum, which may be significant as suggested by recent observations [48], as well as for the coupling of dynein activity with calcium signaling [23,25,49].…”
Section: Discussionmentioning
confidence: 99%
“…Human sperm spinning has been observed to be mono-directed (Linnet, 1979;Smith et al, 2009b;Phillips, 1983;Woolley, 1977), bidirected (Ishijima et al, 1992;Dardikman-Yoffe et al, 2020;Drake, 1974), and even intermittently directed (Bukatin et al, 2015). However, such reported variety in spinning direction appears to contradict observations of a conserved helical beating of human sperm flagellum (Bukatin et al, 2015;Ishijima et al, 1992;Linnet, 1979;Powar et al, 2022;Zhao et al, 2022), and conserved chirality of structural components in mammalian sperm flagella (Fawcett, 1975;Leung et al, 2021), with no agreement as to the direction of rotation reported in earlier studies (Woolley, 1977;Bishop, 1958;Drake, 1974;Yeung and Woolley, 1984;Woolley, 1979;Blokhuis, 1961;Daloglu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis above suggests that it is possible to exploit measurements of viscosities at which 2D-3D transitions in beat patterns to extract quantitative estimates of internal forcing. Recently, a microfluidic device was used to systematically study the effect of varying viscosity on the flagellar waveforms of single sperm cells 57 . Transitional viscosities obtained in such devices could be combined with independent measurements of the bending stiffness and compared with results from detailed simulations that account for features that have been neglected here (e.g.…”
Section: Discussionmentioning
confidence: 99%